Validity of Handout Development Based on Guided Note Taking (GNT) on Mechanical Wave Material - Elvi Qorik Ismiyatun; Tri Ariani; Ovilia Putri Utami Gumay (CV. Dharma Samakta Edukhatulistiwa, 2024)
The purpose of this study is to determine the validity of guided note taking (GNT)-based handouts on mechanical wave materials. This research is a type of Research and Development (R&D) development research using a 4D development model consisting of four stages, namely: the defining stage (define), the design stage (design), the development stage (develop), and the dissemination stage (disseminate). The instrument used is a handout validity questionnaire. Validity assessments are carried out by media, language, and material experts. The results of the validity of media experts were 0.86 with a very valid category, the validity of linguists was 0.87 with a very valid category and the validity of material experts was 0.9 with a very valid category, while the validity of all experts was 0.87 with a very valid category. From the results of research that has been done, it was found that handouts based on guided note taking are feasible to be used to increase students' interest in learning. So it can be concluded that handouts based on guided note taking (GNT) on the resulting mechanical wave material are good and valid and can be used in learning.